Somatostatin Serves a Modulatory Role in the Mouse Olfactory Bulb: Neuroanatomical and Behavioral Evidence - Nocera, Sonia; Simon, Axelle; Fiquet, Oriane; Chen, Ying; Gascuel, Jean; Datiche, Frédérique; Schneider, Nanette; Epelbaum, Jacques; Viollet, Cécile (Frontiers in Behavioral Neuroscience, 2019)
Somatostatin (SOM) and somatostatin receptors (SSTR1 - 4) are present in all olfactory structures, including the olfactory bulb, where SOM modulates physiological gamma rhythms and olfactory discrimination responses. In this work, histological, viral tracing and transgenic approaches were used to characterize SOM cellular targets in the murine olfactory bulb. We demonstrate that SOM targets all levels of mitral dendritic processes in the olfactory bulb with somatostatin receptor 2 (SSTR2) detected in the dendrites of previously uncharacterized mitral-like cells. We show that inhibitory interneurons of the glomerular layer express SSTR4 while SSTR3 is confined to the granule cell layer. Furthermore, SOM cells in the OB receive synaptic inputs from olfactory cortical afferents. Behavioral studies demonstrate that genetic deletion of SSTR4, SSTR2 or SOM differentially affects olfactory performance. SOM or SSTR4 deletion have no major effect on olfactory behavioral performances while SSTR2 deletion impacts olfactory detection and discrimination behaviors. Altogether, these results describe novel anatomical and behavioral contributions of somatostatin, SSTR2 and SSTR4 receptors in olfactory processing.